Analisis Efisiensi Produksi Jagung (Zea Mays L.) Di Desa Pagak, Kecamatan Pagak, Kabupaten Malang - Stefanus Ronaldo Putera Edison (Fakultas Pertanian, 2022)
Based on the regression analysis, the R square value is 0.925, which means the amount of corn production as much as 92,5% is influenced by the variables studied and the remaining 7,5% is influenced by other variables. For the F , the calculated F value is 45,617 which is greater than the F table 2,42. This shows that all independent variables are the number of seeds (X1), ZA fertilizer (X2), urea fertilizer (X3), NPK fertilizer (X4), pesticides (X5), outpouring of work (X6), and total costs (X7). For the t test, the production factor that has a significant effect is the number of seeds (X1) and the amount of NPK fertilizer (X4) because t count of each of these variables is greater than t table. In addition, other production factors have no significant effect because t count is smaller than t table.